Perioperative intravenous S(+)-ketamine for acute postoperative pain in adults: study protocol for a multicentre, randomised, open-label, positive-controlled, pragmatic clinical trial (SAFE-SK-A trial) - Wang, Hong; Duan, Chong-Yang; Huang, Wen-Qi; Zhao, Ping; Zhou, Li-Zhi; Liu, Yan-Hong; Liu, Cun-Ming; Chu, Hai-Chen; Wang, Qiang; Diao, Yu-Gang; Hua, Zhen; Meng, Qing-Tao; et al. (BMJ open, 2021)
IntroductionPostoperative pain remains incompletely controlled for decades. Recently, multimodal analgesia is emerging as a potential approach in the management of postoperative pain. Therein, S(+)-ketamine is appealing as an adjuvant drug in multimodal analgesia due to its unique pharmacological advantages. This pragmatic clinical trial (SAFE-SK-A trial) is designed to investigate the analgesic effect and safety of S(+)-ketamine for acute postoperative pain in adults and explore the optimal strategy of perioperative intravenous S(+)-ketamine in a real-world setting.Methods and analysisThis multicentre, randomised, open-label, positive-controlled, pragmatic clinical trial (SAFE-SK-A study) is planned to conduct in 80 centres from China and recruit a total of 12 000 adult participants undergoing a surgical procedure under general anaesthesia. Patient recruitment started in June 2021 and will end in June 2022. Participants will be randomised in a ratio of 2:1 to either receive perioperative intravenous S(+)-ketamine plus conventional anaesthesia or conventional anaesthesia only. Given the pragmatic nature of the study, no specific restriction as to the administration dosage, route, time, synergistic regimen or basic analgesics. Primary endpoints are the area under the broken line of Numerical Rating Scale (NRS) scores for pain intensity and the total opioid consumption within 48 hours postoperative. Secondary endpoints are postoperative NRS scores, the anaesthesia recovery time, time of first rescue analgesia, the incidence of rescue analgesia, the incidence of postoperative delirium, patient questionnaire for effect, changes from baseline in cognitive function and anxiety and depression, as well as the adverse events and pharmacoeconomic outcomes. The general linear model will be used for the primary endpoint, and appropriate methods will be used for the secondary endpoints.Ethics and disseminationThis trial has been approved by the local Institutional Review Board (S2021-026-02) and conducted following the Declaration of Helsinki. Results of this trial will be publicly disclosed and published in scientific journals.Trial registration numberNCT04837170; Pre-results.